Serum potassium in the crush syndrome victims of the Marmara disaster - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2003)
Background: Hyperkalemia is a major cause of mortality in the patients who suffer from crush syndrome in the aftermath of major earthquakes. The aim of this study is to investigate the frequency and effects of hyperkalemia in the 639 victims of catastrophic Marmara earthquake that struck northwestern Turkey, in August 1999. Patients and methods: Within the first week of disaster, questionnaires were sent to 35 reference hospitals that treated the victims. Information on serum potassium which was provided in 595 out of 639 questionnaires was submitted to analysis. Results: In the patients who were admitted within the first 3 days of the disaster (n = 401) serum potassium was 5.4 +/- 1.3 mEq/l, which was higher than in those admitted thereafter ( n = 171) ( 4.5 +/- 1.1 mEq/l) ( p = 0.02). Considering the whole series, males ( p = 0.01), patients needing dialysis support ( p < 0.001) and non-survivors ( p = 0.001) were characterized by higher serum potassium at admission. Seventy patients' serum potassium was above 7 mEq/l, while 22 patients were hypokalemic (< 3.5 mEq/l). Admission potassium correlated with many clinical and laboratory variables indicating the severity of the trauma, and a logistic regression model with clinical and laboratory parameters upon admission, revealed potassium as the most significant predictor of dialysis needs in the victims admitted within the first 3 days ( p = 0.008, OR = 3.33). Among the victims who were admitted to hospitals 1 week after the disaster, 8 had serum potassium levels above 6.5 mEq/l; among 4 of them were complicated by hyperkalemia even higher than 7.5 mEq/l. These findings undeline the importance of hyperkalemia during clinical course. Conclusion: The most important and fatal medical complication in crush syndrome patients is hyperkalemia. Risk of fatal hyperkalemia continues even after hospitalization. Empirical therapy at the scene is indicated especially in male victims with severe soft tissue traumas. Early detection and treatment of hyperkalemia may improve the final outcome of renal disaster victims.
Keywords: crush syndrome; Marmara earthquake; potassium; ACUTE-RENAL-FAILURE; TRAUMATIC RHABDOMYOLYSIS; NEPHROLOGICAL PROBLEMS; EARTHQUAKE; PROPHYLAXIS; FEATURES